Femininity Versus Feminism: Contemporary Islamic Perspectives on the Essence of Womanhood (American Journal of Islam and Society, 2001)
This essay shows how the concept of womanhood undergoes atransformation in the minds of some western females who convert tothe Muslim faith. With respect to the role of women in Islam, threedifferent groups may be distinguished: “outsiders looking in,” “insiderslooking out;” and “converts to Islam looking around and back.” Withinthe first category, a majority see Islam in terms of oppression andservitude, although for a smaller group the faith represents a return toall that “hearth and home” signifies. The second major groupingconsists of Muslims, many of whom find Muslim womanhood to besuperior to non-Islamic alternatives. But an increasing number seek toliberate females from “the tyranny of Islamic Law.” Those in the thirdcategory were originally “outsiders looking in,” but after a transitionalperiod become “insiders looking out.” The . female converts areoriginally attracted to a feminine ideal that is interpreted through theirown culture and experience. Becoming “insiders” brings exposure toissues of Islamic womanhood which necessitate a re-interpretationof the essence of femaleness, producing what uninitiated westernobservers might call rationalizations but which actually formapologetical replies to objections from unbelievers.